Communication Styles and Marital Satisfaction Among Intertribally Married Adults - Busayo Omolade AJIBOLA; Jamila YUSUF; A. I Idowu; Habibat Bolanle ABDULKAREEM (Journal for Lesson and Learning Studies, 2025)
Intertribal marriages are increasingly common in multicultural societies and present challenges such as cultural differences and language barriers, which can affect marital harmony and satisfaction. These differences may lead to conflict and reduce relationship quality if not managed adaptively. This study aimed to analyze communication styles in intertribal marriages and examine the relationship between communication styles and marital satisfaction based on gender, ethnic background, and length of marriage. The study employed a quantitative approach with a descriptive correlational survey design. The subjects included 389 adults in intertribal marriages. Data were collected using the Communication Styles and Marital Satisfaction Questionnaire with a reliability coefficient of 0.79 and analyzed using descriptive statistics and Pearson’s Product Moment correlation at a 0.05 significance level. Results indicated that avoidance was the most dominant communication style (approximately 40% of respondents), while overall marital satisfaction was high. No significant relationship was found between communication styles and marital satisfaction, nor were there significant differences based on gender, ethnic background, or length of marriage. The findings suggest that marital satisfaction is more strongly influenced by relational factors and cultural sensitivity than by communication style alone. These results imply the importance of strengthening partner attentiveness, emotional support, and cultural accommodation, which can inform counselors, social workers, and psychologists in efforts to enhance harmony and satisfaction in intertribal marriages.